The Concept of Epistemology in Islamic Education and Its Challenges in the Era of Artificial Intelligence - Fitriani Musa; Sahjad M Aksan; Arif Rahman Firianto; Adiyana Adam; B. Baharuddin (Manunggal Halim Jaya, 2026)
The development of Artificial Intelligence (AI) has brought significant changes to the field of education, including Islamic education. These changes have given rise to epistemological challenges related to the nature of knowledge, sources of truth, and the role of humans in the learning process. This study aims to examine the concept of epistemology in Islamic education and analyze the challenges and opportunities of integrating Artificial Intelligence within the context of Islamic education. This study employed a qualitative approach using library research. Data were obtained through document studies of books, journal articles, and relevant scientific sources discussing Islamic epistemology and Artificial Intelligence in education. Data analysis was conducted using content analysis and a descriptive-analytical approach to identify the epistemological differences between Islamic education and AI technology. The study results indicate that the epistemology of Islamic education is holistic and integrative, making revelation, reason, and experience the primary sources of knowledge in Islamic education. Meanwhile, Artificial Intelligence operates within a rational-empirical framework that is instrumental and value-free, thus unable to replace the human role in shaping moral and spiritual values. Therefore, the integration of AI in Islamic education must be conducted critically and selectively, while still making Islamic values the main foundation for achieving the goals of Islamic education, namely, forming individuals who are faithful, knowledgeable, and of noble character.